PENGARUH PENGGUNAAN SMARTPHONE TERHADAP INTERAKSI SOSIAL DAN MINAT BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN IPS - Rustantono, Hendra; Puspita, Elsa Dwi Puspita; Rasyid, Hamidi Rasyid (Universitas Islam Raden Rahmat Malang, 2023)
This research is motivated by the reduced social interaction of social studies study program students as well as the low interest in learning in the lecture environment. One of the factors that influence the low social interaction and interest in learning is the use of smartphones. While the purpose of this research is to determine the effect of smartphone use on student social interaction and to determine smartphone use on student learning interest in social studies education programs. This type of research is included in quantitative research and was carried out at Raden Rahmat Islamic University Malang in the Social Sciences Education Study Program. The results of this research show that there is an effect of smartphone use on social interaction as evidenced by t-count = 4.820 > t-table = 1.669 and significant = 0.000 <0.05. There is an effect of smartphone use on learning interest as evidenced by t-count = 2.779 > t-table = 1.669 also significant = 0.007 <0.05. There is a linear effect of smartphone use on social interaction and learning interest. This can be proven by f-count = 21.545 > f-table = 3.984. The influence of smartphone use on social interaction and learning interest is 37.4%.